Engajamento público em pesquisa como forma de democratização da ciência: revisão de escopo e análise do comportamento - Cruz, Luiz Felipe (2020)
We conducted a scoping review to create an outlook of the literature regarding citizen science and the democratization of science. We also investigated how a perspective based on Behavior Analysis could contributed to such a literature, focusing on methodological aspects and on measuring. From a total of 3.953 publications, only four were included in our final analysis. This result is discussed in relation to definitions of participation and the usage of the word “science” in the literature. Among the four studies that were selected, we identified possibilities and the recommendations for behavior analysts engaging in citizen science, as well as possible methodological input that Behavior Analysis may have to offer. However, in these four studies, we did not identify information that could lead us to elaborate a set of possible behavior measures of public engagement with science and the democratization of science